Prediction of Methyl Orange (MO) Toxicity and Minimizing Its Pollution in Aquatic Environment by Activated Carbon Adsorption - Salwan Sufyan Ibrahim; Safauldeen Adnan; Ammar Salim Manati; Kafa Khalaf Hammud (Iraqi Journal of Industrial Research)
Minimizing environmental pollution is an essential work of the official and scientific communities around the world, especially in water systems. In water, soluble dye works as a blockage in photosynthesis process because of its toxicity. One of these highly applicable dyes in industry is Methyl Orange (MO), documented with more than 10% released to water. Here, a new Iraqi try of converting environmental and health problems to solutions with high quantification was as done by using face tissue (Kleenex) as a carbon source. Primary in Silico testing of this anionic dye (Methyl Orange) was done based on online website confirmed MO dye is unsafe in several toxicological determinations such as foetus health (during pregnancy). Also, it is permeable material to skin, Blood- Brain system (BBB), and Human Colon Carcinoma cell line (CaCO2) compatible with Human Intestinal absorption (74.166%). In experimental section, low quality of face tissue (Kleenex) was subject to a high acidic medium (concentrated sulphuric acid), followed by addition of sodium carbonate to .increase activation of based carbon material with more structural pores yielding high removal efficiency and adsorption capacity ranged (88-98)% and (88-98) mg/g respectively. Qualitative and quantitative evaluations were based upon choosing two wavelengths in ultraviolet (272 nm) and visible (464 nm) regions. In this work, two removal steps were performed with the same adsorbent companied by multiple UV-Vis spectroscopic evaluation of several tested sections. Reviewing of published papers in MO removal presents the extraordinary performance of this prepared material towards using it as an excellent adsorbent of toxic material in aqueous solution.